Multi-modal representation of effector modality in frontal cortex during rule switching - Hodgson, Timothy L.; Parris, Benjamin A.; Benattayallah, Abdelmalek; Summers, Ian R. (Frontiers in Human Neuroscience, 2015)
We report a functional magnetic resonance imaging study which investigated whether brain areas involved in updating task rules within the frontal lobe of the cerebral cortex show activity related to the modality of motor response used in the task. Participants performed a rule switching task using different effector modalities. In some blocks participants responded with left / right button presses, whilst in other blocks left / right saccades were required. The colour of a Cue event instructed a left or right response based upon an rule, followed by a Feedback which indicated whether the rule was to stay the same or “Flip” on the next trial. The findings revealed variation in the locus of activity within the ventrolateral frontal cortex dependent upon effector modality. Other frontal areas showed no significant difference in activity between response epochs but changed their pattern of connectivity with posterior cortical areas dependent upon response. Multivariate analysis revealed that the pattern of activity evoked by Flip rule Feedbacks within an apparently supra modal frontal region (dorsolateral frontal cortex) discriminated between response epochs. The results are consistent with the existence of multi-modal representations of stimulus-response rules within the frontal cerebral cortex.